1984
DOI: 10.1103/physrevb.30.6849
|View full text |Cite
|
Sign up to set email alerts
|

Electron-energy-loss-spectroscopy study of oxygen chemisorption and initial oxidation of Fe(100)

Abstract: The initial stages of the interaction of oxygen with an Fe(100) surface have been investigated at 300 K mainly by electron-energy-loss spectroscopy (EELS) with in situ combined low-energyelectron-diffraction, Auger-electron and secondary-electron-emission spectroscopy, and workfunctionchange measurements {b, P). From all the results, three different stages of the oxygen interaction are distinguished:(i) dissociative chemisorption stage up to -3 L, (ii) incorporation of 0 adatoms into the selvedge between 3 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
2

Year Published

1988
1988
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(25 citation statements)
references
References 36 publications
2
21
2
Order By: Relevance
“…The oxygen uptake curve at Ͻ50 L is similar to that reported for Fe͑100͒ single crystal surfaces. 9,15 Similar to previous studies, 9,15 three stages, i.e., I ͑0-3 L͒, II ͑3-20 L͒ and III ͑Ͼ20 L͒, are also seen in our result. The regions I, II, and III have been assigned to the dissociative chemisorption, oxygen incorporation, and the formation of a three-dimensional oxide, respectively.…”
supporting
confidence: 91%
See 3 more Smart Citations
“…The oxygen uptake curve at Ͻ50 L is similar to that reported for Fe͑100͒ single crystal surfaces. 9,15 Similar to previous studies, 9,15 three stages, i.e., I ͑0-3 L͒, II ͑3-20 L͒ and III ͑Ͼ20 L͒, are also seen in our result. The regions I, II, and III have been assigned to the dissociative chemisorption, oxygen incorporation, and the formation of a three-dimensional oxide, respectively.…”
supporting
confidence: 91%
“…The regions I, II, and III have been assigned to the dissociative chemisorption, oxygen incorporation, and the formation of a three-dimensional oxide, respectively. 15 Our result is however different from that of Sakisaka et al 15 at the high exposure range. They reported that the O/Fe Auger ratio, although it is about 1.3 at ϳ50 L, increases to 2.2 at 350 L. 15 They suggested that the surface oxide at 350 L would be Fe 2 O 3 .…”
contrasting
confidence: 82%
See 2 more Smart Citations
“…Investigations of the initial stages of the interaction of oxygen with an Fe(100) surface have shown [24,25] that oxygen atoms adsorb in the fourfold coordinated hollow sites on Fe(100). These findings were confirmed by density-functional calculations [4,25].…”
Section: Introductionmentioning
confidence: 99%